"If only" counterfactual thoughts about cooperative and uncooperative decisions in social dilemmas. (3rd April 2022) - Pighin, Stefania; Byrne, Ruth M. J.; Tentori, Katya
Abstract: We examined how people think about how things could have turned out differently after they made a decision to cooperate or not in three social interactions: the Prisoner's dilemma (Experiment 1), the Stag Hunt dilemma (Experiment 2), and the Chicken game (Experiment 3). We found that participants who took part in the game imagined the outcome would have been different if a different decision had been made by the other player, not themselves; they did so whether the outcome was good or bad for them, their own choice had been to cooperate or not, and the other player's choice had been to cooperate or not. Participants who only read about a fictional protagonist's game imagined changes outside the protagonist's control (such as the other player's decision) after a good outcome but within the protagonist's control (such as the protagonist's decision) after a bad outcome. The implications for theories of counterfactual thinking and moral decision-making are discussed.